Probing the chirality of a single microsphere trapped by a focused vortex beam through its orbital period - Diniz Kainã; Schoger Tanja; da Fonseca Arthur L.; Dutra Rafael S.; Ether Jr Diney S.; Ingold Gert-Ludwig; Pinheiro Felipe A.; Viana Nathan B.; Neto Paulo A. Maia (Nanophotonics)
When microspheres are illuminated by tightly focused vortex beams, they can be trapped in a non-equilibrium steady state where they orbit around the optical axis. By using the Mie–Debye theory for optical tweezers, we demonstrate that the orbital period strongly depends on the particle’s chirality index. Taking advantage of such sensitivity, we put forth a method to experimentally characterize with high precision the chiroptical response of individual optically trapped particles. The method allows for an enhanced precision at least one order of magnitude larger than that of similar existing enantioselective approaches. It is particularly suited to probe the chiroptical response of individual particles, for which light-chiral matter interactions are typically weak.